2008
DOI: 10.1159/000163851
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of β<sub>3</sub>-Adrenergic Receptor mRNA in Human Colon Cancer: A Preliminary Study

Abstract: Objective: Tumor cell proliferation and migration, as well as metastasis formation, can be affected by several neurotransmitters, which therefore seem to be involved in the most important aspects of the malignant phenotype. In particular, modified β-adrenergic functions seem to be associated with proliferative alterations of numerous cancer cell lines. Pharmacological modulation of β-adrenoceptors (β-ARs) affects tumor cell growth in several experimental systems, and inhibition of metastasis formation by β-AR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Until a few years ago, the β2-AR subtype was identified as the most involved in tumor-related pathways [13]. However, an aberrant expression of the β3-AR subtype has been recently shown in several cancers, such as leukemia, vascular tumors, colon carcinoma [14][15][16], and many other human cancers [17]. Moreover, recent studies have shown that the use of selective β3-AR antagonists in melanoma was effective in reducing tumor growth via direct antitumoral effects [18] and by affecting tumor microenvironment reactivity [19].…”
Section: Introductionmentioning
confidence: 99%
“…Until a few years ago, the β2-AR subtype was identified as the most involved in tumor-related pathways [13]. However, an aberrant expression of the β3-AR subtype has been recently shown in several cancers, such as leukemia, vascular tumors, colon carcinoma [14][15][16], and many other human cancers [17]. Moreover, recent studies have shown that the use of selective β3-AR antagonists in melanoma was effective in reducing tumor growth via direct antitumoral effects [18] and by affecting tumor microenvironment reactivity [19].…”
Section: Introductionmentioning
confidence: 99%
“…β3-AR plays a key role in the pathophysiology of the cardiovascular system and has been recently correlated with de novo angiogenesis in models of retinal vascular proliferation [810]. Moreover, β3-AR mRNA aberrant expression has been reported in human cancers, such as leukemia, vascular tumors and colon carcinoma [5, 11, 12]. Recently, β 3 -ARs has been found to be expressed by murine melanoma B16F10 cells and by endothelial cells of the tumor vasculature [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…A twofold higher expression of b 3 -AR mRNA in cancer tissue than normal one was found, thus suggesting a b 3 -AR possible involvement in the human colon tumor processing (Perrone et al, 2008a). Pharmacological modulation of b-ARs affects tumor cell growth in several experimental systems, and inhibition of metastasis formation by b-ARs antagonists in in vivo models has been ascertained.…”
Section: B 3 -Adrenoceptormentioning
confidence: 98%